Understanding fat, proteins and saliva impact on aroma release from flavoured ice creams - Ayed, Charfedinne; Martins, Sara I.F.S.; Williamson, Ann-Marie; Guichard, Elisabeth (Elsevier, 2017)
The release profile of fourteen aroma compounds was studied in ice cream samples varying in fat and protein, both in level and type. In vitro aroma release was monitored by solid phase micro-extraction gas chromatography using an innovative saliva reactor, which imitated human chewing under temperature control. The results showed that the effect of the fat type on aroma release was smaller than that of fat level. Ice creams with low fat level released more hydrophobic aroma compounds than ice creams with high fat level. At low fat level more aroma compounds were released from ice creams with lower protein content. At high fat level a small increase of aroma release was observed by the addition of saliva, which was explained by a salting out effect, due to the presence of proteins and salts in the saliva. These findings confirmed that the interactions between salivary proteins and aroma compounds occurring in aqueous solutions are not observed in emulsions.